2013
DOI: 10.1371/journal.ppat.1003281
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringae pv. syringae Uses Proteasome Inhibitor Syringolin A to Colonize from Wound Infection Sites

Abstract: Infection of plants by bacterial leaf pathogens at wound sites is common in nature. Plants defend wound sites to prevent pathogen invasion, but several pathogens can overcome spatial restriction and enter leaf tissues. The molecular mechanisms used by pathogens to suppress containment at wound infection sites are poorly understood. Here, we studied Pseudomonas syringae strains causing brown spot on bean and blossom blight on pear. These strains exist as epiphytes that can cause disease upon wounding caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 56 publications
2
61
0
Order By: Relevance
“…Both effectors belong to the YopJ family, which is widespread among animal and plant pathogens but whose members are absent from Pst (Lewis et al, 2011). Also, Pst does not possess SylA, a secreted toxin produced, for instance, by P. syringae pv syringae, which directly targets the catalytic subunits of the 26S proteasome (Groll et al, 2008;Schellenberg et al, 2010;Baltrus et al, 2011;Misas-Villamil et al, 2013). Thus, the suppression of proteasome activity below the basal level by virulent Pst likely involves a previously unidentified effector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both effectors belong to the YopJ family, which is widespread among animal and plant pathogens but whose members are absent from Pst (Lewis et al, 2011). Also, Pst does not possess SylA, a secreted toxin produced, for instance, by P. syringae pv syringae, which directly targets the catalytic subunits of the 26S proteasome (Groll et al, 2008;Schellenberg et al, 2010;Baltrus et al, 2011;Misas-Villamil et al, 2013). Thus, the suppression of proteasome activity below the basal level by virulent Pst likely involves a previously unidentified effector.…”
Section: Discussionmentioning
confidence: 99%
“…Several T3Es from different genera of plant pathogenic bacteria, such as Pseudomonas and Xanthomonas, were shown to suppress plant defense responses by acting as E3 ligases or by promoting ubiquitination and degradation of target proteins (Nomura et al, 2006;Singer et al, 2013;Börnke, 2014, 2015;Banfield, 2015). A more direct way to subvert the UPS is achieved by SylA, a secreted small nonribosomal peptide from Pseudomonas syringae pv syringae, which binds to the catalytic subunits of the 26S proteasome to inhibit its activity and suppress plant immune reactions, including stomatal closure and SA-mediated signaling (Groll et al, 2008;Schellenberg et al, 2010;Misas-Villamil et al, 2013). The first bacterial T3Es identified that directly target the proteasome for defense suppression are XopJ from Xanthomonas campestris pv vesicatoria and HopZ4 from Pseudomonas syringae pv lachrymans.…”
mentioning
confidence: 99%
“…Syringolin A (SylA), a virulence factor and a proteasome inhibitor produced by P. syringae pv syringae, plays a role in defense suppression as evidenced by the inability of sylA mutants to inhibit SA accumulation and associated resistance responses in bean (Table 1) (Groll et al, 2008;Misas-Villamil et al, 2013). SylA reverts PTIassociated stomatal closure that is also dependent on both SA and NPR1 (NONEXPRESSOR OF PATHOGENESIS-RELATED GENES1), a master regulator of SA signaling (Figure 3) (Schellenberg et al, 2010).…”
Section: Effectors Targeting Sa Signalingmentioning
confidence: 99%
“…However, for a bacterial pathogen to cause disease, it must penetrate through the plant epidermis and be able to survive and proliferate inside the plant. The mode and mechanism of penetration into the plant tissue is a critical step for infection, especially for bacterial pathogens that rely on natural openings and accidental wounds on the plant surface to colonize internal tissues (Misas-Villamil et al, 2013). Stomata are an example of such openings, providing one of the main routes through which the foliar pathogen Pseudomonas syringae transitions from avirulent epiphytic to virulent endophytic lifestyles (Melotto et al, 2008).…”
mentioning
confidence: 99%